2009
DOI: 10.1111/j.1478-3231.2009.01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired liver regeneration with humoral and genetic disturbances in urinary trypsin inhibitor‐deficient mice

Abstract: UTI appears to important cytokine and chemokine regulation in normal liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Impairment of liver regeneration was observed in UTI −/− mice with high cytokine and chemokine levels [47]. Multiple pharmacological properties that may contribute to inhibition of MMPs during advanced stages of liver regeneration, and there may be a dynamic inhibition-promoting balance that is regulated by inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of liver regeneration was observed in UTI −/− mice with high cytokine and chemokine levels [47]. Multiple pharmacological properties that may contribute to inhibition of MMPs during advanced stages of liver regeneration, and there may be a dynamic inhibition-promoting balance that is regulated by inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Ulinastatin or urinary trypsin inhibitor (UTI) is a Kunitz-type serine protease inhibitor that plays an antiinflammatory effect by inhibiting several proteases such as trypsin, plasmin, cathepsin G, chymotrypsin, and neutrophil elastase (6). Animal studies (7)(8)(9)(10) and human studies (11,12) showed that UTI administration suppressed acute inflammatory responses after hepatectomy. Since there was no systematic review or meta-analysis of randomized controlled trials (RCTs) to assess the benefits of UTI in hepatectomy, whether perioperatively UTI using has a protective effect on liver function remained unclear.…”
Section: Original Articlementioning
confidence: 99%
“…On the other hand, a large number of in vivo reports have provided evidence that UTI protects against pathological traits related to septic shock induced by gram-negative bacteria: UTI reduces LPS-induced hypoten- using UTI (-/-) mice via the regulation of systemic (serum) levels of cytokines such as IL-6 and IL-10 and chemokines such as MCP-1 and MIP-1α 73 .…”
Section: Anti-inflammatory Property Of Utimentioning
confidence: 99%